2015
DOI: 10.1016/j.psyneuen.2014.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in acute hormonal and subjective response to naltrexone: The impact of menstrual cycle phase

Abstract: Women often exhibit larger hormonal and subjective responses to opioid receptor antagonists than men, but the biological mechanisms mediating this effect remain unclear. Among women, fluctuations in estradiol (E2) and progesterone (P4) across the menstrual cycle (MC) affect the endogenous opioid system. Therefore, the goal of the current study was to compare acute naltrexone response between women in the early follicular phase of the MC (low E2 and P4), women in the luteal phase of the MC (high E2 and P4), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 78 publications
1
44
0
Order By: Relevance
“…These factors may impinge on associations between naltrexone-induced nausea and hedonic eating behavior, and deserve further attention. In addition, the naltrexone-induced cortisol increases and nausea were not highly correlated, as found in earlier studies (e.g., Daubenmier et al, 2014; Roche and King, 2015). Opioidergic systems governing subjective responses such as nausea may be separate from hypothalamic opioid tone.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…These factors may impinge on associations between naltrexone-induced nausea and hedonic eating behavior, and deserve further attention. In addition, the naltrexone-induced cortisol increases and nausea were not highly correlated, as found in earlier studies (e.g., Daubenmier et al, 2014; Roche and King, 2015). Opioidergic systems governing subjective responses such as nausea may be separate from hypothalamic opioid tone.…”
Section: Discussionsupporting
confidence: 70%
“…Opioidergic systems governing subjective responses such as nausea may be separate from hypothalamic opioid tone. Indeed, the gastrointestinal tract is home to several endogenous opioidergic actions, and direct action on this opioidergic system could contribute to naltrexone-induced nausea (Holzer, 2009; Roche & King, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women show variations in cortisol stress reactivity as a function of the menstrual cycle (Kudielka et al, 2009) and use of hormonal contraceptives (Kirschbaum et al, 1999;Roche et al, 2013). Similarly, cortisol response to naltrexone is larger during the luteal phase of the menstrual cycle relative to the follicular phase (Roche and King, 2015). We have reported that women as a group have large cortisol responses to 50 mg naltrexone relative to men (Lovallo et al, 2012), suggesting a greater degree of mu-opioid receptor restraint over the endogenous activity of the HPA in women that attenuates stress reactivity and is unmasked by opioid antagonism.…”
Section: Discussionmentioning
confidence: 99%
“…Excluding polysubstance use could have yielded a more homogeneous sample but would not be representative of the clinical OUD population (Wang et al, 2015). Finally, the between-subject variability in the menstrual cycle phase across scan sessions in this outpatient study could obscure the possible reproductive hormone-related effects (Carroll, Lynch, Roth, Morgan, & Cosgrove, 2004; Roche & King, 2015; Sprengelmeyer et al, 2009). Controlling for the menstrual cycle phase in a patient population may require a more structured environment than an outpatient setting could offer.…”
Section: Discussionmentioning
confidence: 97%